Survey, of physiological races of the wheat leaf rust (Puccinia recondita) in southern Brazil - Coelho, Elisa Thomaz; Barcellos, Amarilis Labes; Silva, Ady Raul da (Pesquisa Agropecuaria Brasileira, 2014)
From 1958 to 1969, a total of 1906 isolates of the wheat leaf rust fungus (Puccinia recondita Rob. ex. Desm.) were made from material collected in the wheat-growing regions of southern Brazil. In order to differentiate the races of the fungus, a group of wheat cultivars of regional interest was used. The isolates were classified as races using the prefix IAS 58. The following IAS 58 races were determined; 2, 2A, 4, 4A, 6, 7, 7A, 10, 10A, 11, 16, 17, 19, 19A, 20, 20A, 21, 21A, 22, 22A, 24, 24A, 25, 26, and 27. The races 25 and 26 were first determined on samples collected in 1961, and race 27 in 1962. Races and subraces of groups 19 and 4 as a rule predominated. With the exception of those of group 2, other races and subraces appeared only sporadically.